Study of proton radiation effects among diamond and rectangular gate MOSFET layouts. (13th January 2017) - Seixas, L E; Finco, S; Silveira, M A G; Medina, N H; Gimenez, S P
Abstract: This paper describes an experimental comparative study of proton ionizing radiation effects between the metal-oxide-semiconductor (MOS) Field Effect Transistors (MOSFETs) implemented with hexagonal gate shapes (diamond) and their respective counterparts designed with the classical rectangular ones, regarding the same gate areas, channel widths and geometrical ratios (W/L). The devices were manufactured by using the 350 nm bulk complementary MOS (CMOS) integrated circuits technology. The diamond MOSFET with α angles higher or equal to 90° tends to present a smaller vulnerability to the high doses ionizing radiation than those observed in the typical rectangular MOSFET counterparts.